Question 1: Simplify the Boolean expression A + A'B.
Solution: A + B
- A + A'B is simplified using the Distributive Law: A + A'B = A + B.
- This happens because A + A' = 1, and 1B = B.
Question 2: Simplify the Boolean expression A(A + B).
Solution: A
- Using the Distributive Law: A(A + B) = AA + AB.
- Since AA = A, the expression becomes A + AB.
- Using Absorption Law: A + AB = A.
Question 3: Simplify the Boolean expression A' + AB.
Solution: A' + B
- Using Distributive Law: A' + AB = (A' + A)(A' + B).
- Since A' + A = 1, the expression simplifies to 1(A' + B) = A' + B.
Question 4: Simplify the Boolean expression AB + A'B.
Solution: B
- Using the Distributive Law: AB + A'B = B(A + A').
- Since A + A' = 1, the expression simplifies to B.
Question 5: Simplify the Boolean expression (A + B)(A + B').
Solution: A
- Using the Distributive Law: (A + B)(A + B') = A(A + B') + B(A + B').
- Simplifying further: A(A + B') = A, and B(A + B') = B' + B = 1.
- Thus, the entire expression simplifies to A.
Question 6: Simplify the Boolean expression A + AB'.
Solution: A + B'
- Using the Distributive Law: A + AB' = A(1 + B').
- Since 1 + B' = 1, the expression simplifies to A + B'.
Question 7: Prove that A + A' = 1.
Solution: 1
- A + A' is an axiom in Boolean algebra known as the Complement Law.
- The sum of a variable and its complement is always equal to 1.
Question 8: Simplify the Boolean expression A'B + AB'.
Solution: A ⊕ B (A XOR B)
- This is the standard expression for XOR (exclusive OR): A ⊕ B = A'B + AB'.
Question 9: Simplify the Boolean expression A' + AB + A'C.
Solution: A' + B + C
- Using the Distributive Law: A' + AB + A'C = A'(1 + C) + AB.
- Since 1 + C = 1, the expression simplifies to A' + AB = A' + B.
- The result is A' + B + C.
Question 10: Simplify the Boolean expression AB + A'B + AB'.
Solution: A + B
- Using the Distributive Law: AB + A'B + AB' = B(A + A') + AB'.
- Since A + A' = 1, the expression simplifies to B + AB' = A + B.
Question 11: Simplify the Boolean expression (A + B)(A + C).
Solution: A + BC
- Using the Distributive Law: (A + B)(A + C) = A(A + C) + B(A + C).
- Simplifying: A + AC + AB + BC = A + AB + BC.
- Using Absorption: A + AB = A, so the expression becomes A + BC.
Question 12: Simplify the Boolean expression A'B + AB.
Solution: B
- Using the Distributive Law: A'B + AB = B(A' + A).
- Since A' + A = 1, the expression simplifies to B.
Question 13: Prove that A + 0 = A.
Solution: A
- This is a Boolean algebra axiom called the Identity Law.
- The OR operation with 0 does not affect the value of A, so A + 0 = A.